2012
DOI: 10.1111/j.1502-3885.2012.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

A robust feldspar luminescence dating method for Middle and LatePleistocene sediments

Abstract: Luminescence dating is used extensively to provide absolute chronologies for Late Pleistocene sediments. Nowadays, most optical dates are based on quartz optically stimulated luminescence (OSL). However, the application of this signal is usually limited to the last ∼100 ka because of saturation of the quartz luminescence signal with dose. In contrast, the feldspar infrared stimulated luminescence (IRSL) dose–response curve grows to much higher doses; this has the potential to extend the datable age range by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
470
3
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 638 publications
(553 citation statements)
references
References 72 publications
33
470
3
13
Order By: Relevance
“…This is consistent with earlier reports that elevated temperature pIRIR signals are more difficult to bleach than the IR 50 signal (e.g. Sohbati et al, 2012c;Buylaert et al, 2012;Kars et al, 2014). On closer inspection, one can see a step in the luminescence profiles of both signals; at about ~4-5 mm for the pIRIR 225 signals and ~4-10 mm for the IR 50 .…”
Section: Was the Cobble Surface Bleached?supporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with earlier reports that elevated temperature pIRIR signals are more difficult to bleach than the IR 50 signal (e.g. Sohbati et al, 2012c;Buylaert et al, 2012;Kars et al, 2014). On closer inspection, one can see a step in the luminescence profiles of both signals; at about ~4-5 mm for the pIRIR 225 signals and ~4-10 mm for the IR 50 .…”
Section: Was the Cobble Surface Bleached?supporting
confidence: 79%
“…This argument is based on the widely-observed differential bleaching rates of quartz and feldspar signals (e.g. Godfrey-Smith et al, 1988;Thomsen et al, 2008;Buylaert et al, 2012;Murray et al, 2012;Sugisaki et al, 2015;Colarossi et al, 2015) when exposed to a daylight spectrum, and helps to quantitatively address one of the main uncertainties in the application of OSL to dating.…”
Section: K-rich Feldsparmentioning
confidence: 99%
“…Sohbati et al (2012) observed an increase in the pIRIR(225) residual doses with the D e values of their samples. A similar observation was made by Buylaert et al (2012) for the pIRIR(290) signals of 15 samples, and they suggested that the residual doses at the time of burial may be smaller than the residual doses inferred from laboratory measurements. Reimann and Tsukamoto (2012) found that the residual doses associated with the 50°C IRSL and pIRIR (150) signals were the same after a prolonged bleach, although the pIRIR signal is thought to be bleached more slowly than the 50°C IRSL signal.…”
Section: Introductionmentioning
confidence: 51%
“…In such contexts, feldspar IRSL often provides an alternative, although this signal is known to suffer from anomalous fading, causing age underestimation (Wintle, 1973;Huntley and Lamothe, 2001). To circumvent the problem of fading, new approaches involve using a thermally-assisted IRSL measurement (post-IR IRSL; Thomsen et al 2008;Buylaert et al, 2012). However, this signal is known to bleach less rapidly and can cause ageoverestimation in proglacial environments (Blomdin et al, 2012;Lowick et al, 2012).…”
Section: Luminescence Datingmentioning
confidence: 99%